Penerapan Metode Inquiry Learning Terhadap Kemampuan Berpikir Kritis Siswa Dalam Pembelajaran Fiqih Di Mts Al-Isro’: The Application of Inquiry Learning in Improving Students’ Critical Thinking Skills in Fiqh Learning at Islamic Junior High School Al-Isro’ - Ahmad Syauqi Futaqi; Abdul Rozaq (Educan, 2026)
This study examines the implementation of the Inquiry Learning method in Fiqh instruction at MTs Al-Isro’, focusing on material that requires students to engage in analytical thinking and deepen their conceptual understanding. The primary aim is to evaluate the extent to which the inquiry approach enhances student participation, strengthens critical thinking skills, and fosters a learning environment that is more exploratory and student-centered. Employing a qualitative case study design, the research draws on classroom observations, interviews with the Fiqh teacher, and an analysis of relevant instructional documents. The findings reveal that the structured stages of inquiry from identifying problems and gathering information to testing understanding and drawing conclusions effectively encourage students to formulate questions, assess arguments more carefully, and relate lesson content to real-life contexts. The success of this approach is supported by the teacher’s readiness to present relevant Fiqh cases and by the use of group discussions to reinforce understanding. Nevertheless, challenges such as limited instructional time and varying levels of students’ initial abilities remain, highlighting the need for more targeted scaffolding strategies. Overall, the study demonstrates that Inquiry Learning holds substantial potential for improving the quality of Fiqh education by promoting active engagement, deeper reasoning, and more meaningful learning experiences for students.